Assessment of sperm morphological abnormalities, livability and plasmallemalintegrity in frozen-thawed semen of Sahiwal bulls - MANDAL, D K; KUMAR, M; TYAGI, S (The Indian Journal of Animal Sciences, 2011)
Bull-wise total sperm abnormalities ranged from 11.20 to 26.60%. Among the major sperm abnormalities incidences of deformed/degenerated head, pyriform head, asymmetric contour, segmental aplasia of mitochondrial sheath, double mid piece, proximal protoplasmic droplets, Dag defect, double tail, tail looped over head and stump tail were reconded. Among minor abnormalities incidences of free head, narrow head, abaxial implantation of mid piece, bent, coiled, broken, filiform mid piece, transdroplet, coiled tail, bent tail and distal protoplasmic droplets were observed. Minor abnormalities were predominant over major and on overall basis minor abnormalities were 5-time higher than major. Sahiwal bulls showed significant differences among themselves with respect to post-thaw sperm motility, livability, plasmallemal integrity and incidences of various kinds of sperm abnormalities.